WOMEN'S RIGHTS AND GENDER EQUALITY IN STUDENT EDUCATION (Academia Science Repository, 2023)
The article analyzes the problems of the development of the folk tradition in gender education, in the national legislation of universally recognized international norms on the elimination of all forms of discrimination of women's rights, monitoring the implementation in practice of the norms of international documents on gender equality, to which the Republic of Uzbekistan is attached and the implementation of the recommendations established therein.